North Star 1: Listening and Speaking - Merdinger, Polly. Barton, Laurie (New York (State) : Pearson-Longman, 2009)
Trata de mejorar su compresión y expresión oral en situaciones cotidianas.
1. Faraway friends 2. Recycled Fashion
incluye índice
Col. Educ
Keywords: 1. THE BEAUTIFUL GAME 2. TOGETHER IS BETTER